Whistleblowing System, Religiosity, and Financial Reporting Compliance on Fraud Prevention in Village Fund Management - Nur, Sri Wahyuni; Ramadhani, Putri Ayu; Supardi, Haikal (Balance Vocation Accounting Journal, 2024)
The high number of fraud cases in the management of village funds, both at the central and regional government levels in Indonesia, demands early detection steps to prevent these irregularities. One effort is to evaluate the role of the whistleblowing system, religiosity, and financial reporting compliance. This research aims to measure the extent to which these three variables influence fraud prevention in village fund management. The research used a quantitative approach and was carried out in eight villages in Bontoa District, Maros Regency, South Sulawesi Province, involving 40 respondents as samples. Multiple regression analysis was used to process the data obtained. The research results reveal that the whistleblowing system and financial reporting compliance have a positive and significant influence in preventing fraud. However, religiosity does not show a significant contribution to fraud prevention. This study makes an important contribution to related literature, by integrating these variables into the context of village fund management, especially in specific areas such as Bontoa District, which has not been the focus of many previous studies